Supraclavicular artery flaps for head and neck reconstruction: a prospective study - Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand Prasath (International Surgery Journal, 2020)
Reconstruction of defects of the head and neck remains a challenge to the reconstructive surgeon. This is due to the complex anatomy of the region as well as the age and comorbidities of the patients, which prevent the use of free tissue transfer as the primary tool of reconstruction. The supraclavicular artery (SCA) island flap is a well vascularised tissue and provides a thin and pliable skin for cutaneous and mucosal defects of the head and neck region. Here, we had done this flap for eight patients with no major complications and hence, we concur that it is a safe, reliable and versatile reconstructive option for these defects. The study period was from January 2015 to June 2016 where we operated on 8 patients, 5 for post burn contracture neck and 3 for post oncologic resection. The flap was used as a pedicled fascio-cutaneous and was based on the transverse supraclavicular artery. Eight cases underwent supraclavicular artery flap of which 5 were males and 3 females. Mean defect size was 15×10 cm. All the donor sites were closed with a split skin graft. One patient had distal necrosis which was managed with debridement and secondary suturing. The supraclavicular artery flap is a thin, versatile, reliable and easy to harvest flap for reconstructing head and neck defects, with good cosmetic and functional outcome.